The Adoption of Cohesive Devices (CDs) in Indonesian Students of EFL’s Opinion Essays - Rahmadi Nirwanto (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2021)
This study aims at investigating the types of cohesive devices (CDs) and the errors in using cohesive devices (CDs) in opinion essays made by the Indonesian students of EFL.The subjects were twenty-six (26) undergraduate program students of EFL enrolled in an Argumentative writing class. To get the data, they were asked to write an opinion essay which consists of five paragraphs (including introductory and concluding paragraph). After the data were collected, each of the students’ paper was read to identify the use of cohesive devices based on the theory of cohesion proposed by Halliday and Hasan (1976). Then, the number, the frequency and the percentage of cohesive devices were counted. The results of the study revealed that reference had the highest percentage (52.04%), followed by lexical cohesion (32.95%) and conjunction (15.02%). Meanwhile, substitution and ellipsis were absent. Although there were three types of cohesive to be used, the errors still happened in small number such as in conjunction; but, so, or and and.